TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PERUBAHAN FIIK PUBERTAS PADA SISWI SMP NEGERI 5 SUKOHARJO - Agung Widyastuti; Roza Putri Anggraini; Mursudarinah (Universitas Duta Bangsa Surakarta, 2021)
Introduction: The physical changes of puberty cause awkwardness for adolescents because they have to adjust to the changes that occur in them. Striking body growth, for example, rapid breast enlargement, makes teenagers feel ashamed and excluded from their friends. The results of the preliminary study on January 27, 2015 conducted interviews with 20 students of SMP Negeri 5 Sukoharjo 9 (33.3%) of whom only knew about the physical changes of puberty and were still embarrassed by the changes, 6 (23%) students only knew about puberty, and 5 (20%) students do not know anything about the physical changes of puberty Objective: to determine the level of knowledge of young women about the physical changes of puberty in SMP Negeri 5 Sukoharjo. Methods: The research design is descriptive quantitative. The sample is all students at SMP Negeri 5 Sukoharjo as many as 83 respondents. Sampling technique is a non-probability sampling technique by means of saturated sampling (total sampling). The research instrument was a closed questionnaire using univariet analysis. Results: The results showed that the level of knowledge of young women about physical changes in puberty in SMP Negeri 5 sukoharjo students in the good category was 7 students (8.4%), the sufficient category was 55 students (66.2%), and the poor category was 21 students ( 25.3%) Conclusion: The Knowledge Level of Young Women About Physical Changes in Puberty in SMP Negeri 5 Sukoharjo in good, sufficient and poor categories